2020
DOI: 10.3168/jds.2019-17135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abomasal infusion of essential fatty acids and conjugated linoleic acid on performance and fatty acid, antioxidative, and inflammatory status in dairy cows

Abstract: The objective of this study was to test the effects of essential fatty acids (EFA), particularly α-linolenic acid, and conjugated linoleic acid (CLA) supplementation on fatty acid (FA) composition, performance, and systemic and hepatic antioxidative and inflammatory responses in dairy cows. Four cows (126 ± 4 d in milk) were investigated in a 4 × 4 Latin square and were abomasally infused with 1 of the following for 6 wk: (1) coconut oil (control treatment, CTRL; 38.3 g/d; providing saturated FA), (2) linseed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 91 publications
(138 reference statements)
7
48
0
Order By: Relevance
“…Baumgart et al [42] indicated that abomasal infusion of 3.5, 7, and 14 g/d of trans-10,cis-12 CLA in cows for five days decreased milk fat concentration by 24%, 37%, and 46%, respectively, while both isomers trans-10,cis-12 and cis-9,trans-11 CLA decreased milk fat concentration by 28%, 40.8%, and 38.6%-58.1%, respectively, in the studies by Urrutia and Harvatine [20], Vyas et al [43], and Haubold et al [7]. In the experiment by Dohme-Meier and Bee [44], the supplementation of unprotected CLA decreased fat content in cow milk by 53.8%.…”
Section: Fat Contentmentioning
confidence: 85%
See 2 more Smart Citations
“…Baumgart et al [42] indicated that abomasal infusion of 3.5, 7, and 14 g/d of trans-10,cis-12 CLA in cows for five days decreased milk fat concentration by 24%, 37%, and 46%, respectively, while both isomers trans-10,cis-12 and cis-9,trans-11 CLA decreased milk fat concentration by 28%, 40.8%, and 38.6%-58.1%, respectively, in the studies by Urrutia and Harvatine [20], Vyas et al [43], and Haubold et al [7]. In the experiment by Dohme-Meier and Bee [44], the supplementation of unprotected CLA decreased fat content in cow milk by 53.8%.…”
Section: Fat Contentmentioning
confidence: 85%
“…(a) Means of fat and fatty acid content of total lipids of milk from cows that were fed the two diets (CTRL and EXP) at the three sampling times (7, 14, and 30 d). (b) Means of fatty acid (FA) groups with varying degrees of saturation and carbon chain length, desaturase index, and atherogenic index of milk from cows that were fed the two diets (CTRL and EXP) at the three sampling times (7 3 SEM, standard error of the mean; 4 probability of significant effects due to diet (D), time (T), and their interaction (D × T); * p < 0.05, ** p < 0.01, NS, not significant; 5 SFAs, saturated fatty acids; 6 SCFAs, short-chain fatty acids (FAs with C4-10); 7 MCFAs, medium-chain fatty acids (FAs with C12-16:0); 8 MUFAs, monounsaturated fatty acids; 9 PUFAs, polyunsaturated fatty acids; 10 Σ, CLA cis-9,trans-11; trans-10,cis-12; trans-9,cis-11; trans-11,cis-13 and trans-11,trans-13; 11 DI, desaturase index represents the ratio of product and substrate for ∆ 9 -desaturase (double bonds are in the cis orientation unless otherwise indicated); 12 AI, atherogenic index calculated from (C12:0 + (4 x C14:0) + C16:0)/(MUFAs + PUFAs). 3 SEM, standard error of the mean; 4 probability of significant effects due to diet (D), time (T), and their interaction (D × T); * p < 0.05; ** p < 0.01; NS, not significant; 5 SFAs, saturated fatty acids; 6 SCFAs, short-chain fatty acids (FAs with C4-10); 7 MCFAs, medium-chain fatty acids (FAs with C12-16:0); 8 MUFAs, monounsaturated fatty acids; 9 PUFAs, polyunsaturated fatty acids; 10 Σ, CLA cis-9,trans-11; trans-10,cis-12; trans-9,cis-11; trans-11,cis-13 and trans-11,trans-13; 11 DI, desaturase index represents the ratio of product and substrate for ∆ 9 -desaturase (double bonds are in the cis orientation unless otherwise indicated); 12 AI, atherogenic index calculated from (C12:0 + (4 x C14:0) + C16:0)/(MUFAs + PUFAs).…”
Section: Experiments Design Measurements and Sampling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of MDA produced by lipid peroxidation by ROS is also a marker for oxidative stress, thus, the greater concentration of MDA in response to exogenous SFA in the present study underscored the existence of serious oxidative stress. In vivo study, mid-lactating cows was supplemented SPA, α-linolenic acid, and conjugated linoleic acid for 6 weeks, respectively, it was found that SFA supplemented cows showed more serious oxidative stress with a lower plasma glutathione peroxidase activity than in α-linolenic acid, and lower plasma concentration of β-carotene than in α-linolenic acid and conjugated linoleic acid (36). Our previous in vitro studies confirmed that increases in ROS during mitochondrial metabolism can further enhance ER stress (37).…”
Section: Discussionmentioning
confidence: 99%
“…Forty German Holstein-Friesian cows at 18th week of gestation in their 2nd lactation were kept in a free-stall barn at the Leibniz Institute for Farm Animal Biology (FBN), Dummerstorf, Germany. Cows included in the study were surgically fitted with rumen fistulas and abomasal tubes to bypass rumen derived biohydrogenation of supplemented FA (17). The cows were studied in 5 blocks each consisting of 8 cows (2 cows per supplementation group and per block) from week 9 ante partum (ap) up to week 8 post-partum (pp) in their 3rd lactation.…”
Section: Animals and Dietary Supplementationmentioning
confidence: 99%